Mediating effect of job satisfaction on relationship between leader attributes and employee loyalty among public administrators in Malaysia - Mohamed Anwar, Mohamed Afiq (2016)
Previous research shows that employee loyalty is crucial for an organization. Literature shows that factors that contribute to employee loyalty include job decision making, rewards and recognition, and job satisfaction. Also, leader attributes can influence employee loyalty. Studies done on the relationship between leadership factors that contribute to employee loyalty and job satisfaction is scarce particularly those done in Malaysia. The general objective of the study was to determine the level of employee loyalty among Generation Y (Gen Y) Management and Professional group in the Malaysian public service. The study also examines the relationship between employee loyalty, job satisfaction and leader attributes. The study further examined the perception of Gen Y public administrators of their leader attributes (behavior, personality and communication) and whether or not this leader attributes (behavior, personality and communication skill) influence employee loyalty. Job satisfaction was included to determine mediation effect between this relationship. This study employs SEM to analyze the data. The sample of the study is the Gen Y of the Management and Professional group from the Malaysian public sector located in Putrajaya. It involves 495 respondents from eight (8) ministries in Putrajaya. Instruments administered for the research were adopted from Employee Loyalty Acid Test and Loyalty Scale, Mohrman-Cooke-Mohrman Job Satisfaction Scale (MCMJSS), Leadership Practice Index (LPI), USM Personality Inventory (USMaP-i) and Communication Competence Questionnaire (CCQ). All the instruments had high reliabilites. The result of the study showed that leader personality had no significant relationship between employee job satisfaction and employee loyalty. However, there is a strong significant relationship between leader behavior and leader communication skill with employee loyalty. Finally, employee job satisfaction was found to partially mediate the relationship between leader behavior and leader communication skill with employee loyalty. Contribution of the study to literature is contrary to existing studies, where the relationship between job satisfaction and loyalty was found not to be significant. This may indicate that job satisfaction may not be a pertinent factor among Gen Y public administrators to be loyal. What could be more important are the leader behavior and communication skills. The study suggests that the public sector organization to create awareness and where required training among the leaders on increasing behavior and good communication skill that would garner loyalty among the public administrators. Future research may conduct a similar on the private sector for the group of administrators among Gen Y.